Enhancing Teacher Quality: The Role of Digitalization in Transforming Educational Supervision - Herry Sanoto; Dani Kusuma; Mila Chrismawati Paseleng (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to develop a system-based academic supervision model to address specific inefficiencies in the supervision process, such as logistical challenges and resource limitations. The purpose of this research is to develop a system-based academic supervision model in overcoming the ineffectiveness of the academic supervision process. The method in this research is development research using the Borg and Gall model which consists of 10 steps of product development from preliminary research to product dissemination . The research subjects were teachers and school supervisors in Salatiga City, especially in elementary schools consisting of public and private schools. The selection of subjects is based on subjects with criteria, namely subjects who play an active role in the academic supervision process and have experience in academic supervision at school. The instruments in this study were observation guidelines, interview guidelines, user perception questionnaire, and product trial questionnaire. The research instruments have been validated by expert validators and meet the criteria of valid and reliable. The results showed that the development of the Management Information System for academic supervision of the Borg and Gall model resulted in a product that met the criteria of valid, effective and practical for academic supervision. The research findings show that using the academic supervision system makes it easier for supervisors and teachers to carry out the academic supervision process. In addition, the efficiency of supervision becomes better, because it can overcome the distance and the limited number of supervisors to the number of schools whose ratio is not balanced.In addition, the use of an academic supervision system speeds up the supervision process, simplifies the use of assessment instruments, and is practically used flexibly.